2022
DOI: 10.3390/galaxies10010009
|View full text |Cite
|
Sign up to set email alerts
|

Eclipsing Binaries in Dynamically Interacting Close, Multiple Systems

Abstract: Close, compact, hierarchical, and multiple stellar systems, i.e., multiples having an outer orbital period from months to a few years, comprise a small but continuously growing group of the triple and multiple star zoo. Many of them consist of at least one eclipsing pair of stars and, therefore, exhibit readily observable short-term dynamical interactions among the components. Thus, their dynamical and astrophysical properties can be explored with high precision. In this paper we present an overview of the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 207 publications
(284 reference statements)
2
7
0
Order By: Relevance
“…The rather rough and partially incorrect analysis of Lacy et al (1999) let these authors to predict that the eclipses of V907 Sco will start again in 2030 ± 5 in their concluding Section 4. However, Borkovits (2022) noted that the recent observations of TESS have already revealed an onset of V907 Sco eclipses in the Sector 13 data (in mid 2019), and confirmed their expected trend toward deeper eclipses in the Sector 39 data (in mid 2021). Clearly, the situation demands a new analysis of V907 Sco, as the recent emergence of its eclipsing state alone proves that some assumptions and/or data treatment in Lacy et al (1999) have not been correct.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The rather rough and partially incorrect analysis of Lacy et al (1999) let these authors to predict that the eclipses of V907 Sco will start again in 2030 ± 5 in their concluding Section 4. However, Borkovits (2022) noted that the recent observations of TESS have already revealed an onset of V907 Sco eclipses in the Sector 13 data (in mid 2019), and confirmed their expected trend toward deeper eclipses in the Sector 39 data (in mid 2021). Clearly, the situation demands a new analysis of V907 Sco, as the recent emergence of its eclipsing state alone proves that some assumptions and/or data treatment in Lacy et al (1999) have not been correct.…”
Section: Introductionsupporting
confidence: 59%
“…A plethora of dynamical effects at various timescales can be detected with accurate photometric measurements for CHTs, and if properly interpreted with theoretical modeling, they may bring interesting constraints on many physical parameters of the system. An excellent review of this topic was recently published by Borkovits (2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hajdu et al (2019) and Hajdu et al (2022) identified 177 and 16 such CHTs, respectively, using data obtained by the OGLE (Optical Gravitational Lensing Experiment) survey. A recent comprehensive review of the different methods and results of the field of discovering compact hierarchical systems can be found in Borkovits (2022).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is hardly surprising that before the era of the long-duration, ground-based and space-borne photometric surveys, EDVs were (serendipitously) detected in only fewer than a dozen EBs (see the recent review of Borkovits 2022). In contrast to this, Kirk et al (2016) listed 43 EBs in the original Kepler sample which exhibit EDVs.…”
Section: Introductionmentioning
confidence: 99%